2012
DOI: 10.1182/blood-2011-11-394304
|View full text |Cite
|
Sign up to set email alerts
|

EPO-mediated expansion of late-stage erythroid progenitors in the bone marrow initiates recovery from sublethal radiation stress

Abstract: Erythropoiesis is a robust process of cellular expansion and maturation occurring in murine bone marrow and spleen. We previously determined that sublethal irradiation, unlike bleeding or hemolysis, depletes almost all marrow and splenic erythroblasts but leaves peripheral erythrocytes intact. To better understand the erythroid stress response, we analyzed progenitor, precursor, and peripheral blood compartments of mice post-4 Gy total body irradiation. Erythroid recovery initiates with rapid expansion of late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 50 publications
4
56
0
Order By: Relevance
“…1SA). In fact, mouse spleen is a key site for extramedullary erythropoiesis in response to either stress erythropoiesis (4,42). No significant differences in the process of terminal erythroid differentiation between control and Prx2 -/-bone marrow were evident ( Fig 1B).…”
Section: Prx2 -/-Mice Show Ineffective Erythropoiesismentioning
confidence: 80%
“…1SA). In fact, mouse spleen is a key site for extramedullary erythropoiesis in response to either stress erythropoiesis (4,42). No significant differences in the process of terminal erythroid differentiation between control and Prx2 -/-bone marrow were evident ( Fig 1B).…”
Section: Prx2 -/-Mice Show Ineffective Erythropoiesismentioning
confidence: 80%
“…In fact, we have found that after genotoxic injury, a wave of proerythroblasts within the murine BM transition to orthochromatic erythroblasts in just 48 hours. 43 A set of several thousand core erythroid genes composed of tissue-restricted transcripts are expressed in the primitive, fetal definitive, and adult definitive erythroid lineages. Surprisingly, we found no evidence that these transcripts were preferentially retained compared with non-tissue-restricted or housekeeping genes during the terminal stages of erythroid maturation.…”
Section: Discussionmentioning
confidence: 99%
“…82,83 Increased Epo levels are associated with further induction of BclxL and suppression of Bim and Fas-FasL, with a net increase in the number of erythoid progenitors surviving and proliferating. 82,83 In addition, the downstream transcription factor Stat5 can increase erythoid iron intake through Irp2-mediated increased Tfr1 translation. In SE, however, additional proteins and mechanisms are required that do not seem to be essential to steady-state erythropoiesis.…”
mentioning
confidence: 99%